Laboratory Rearing and Niche Resources of Pseudacteon spp. Coquillett (Diptera: Phoridae) Parasitoids of Solenopsis saevissima (Smith) (Hymenoptera: Formicidae) - Marcos Antônio Pesquero; Ana Paula de Almeida Vaz; Filipe Viegas de Arruda (Sociobiology)
Solenopsis saevissima (Smith) is associated with a group of nine Pseudacteon Coquillett species in Brazil.Pseudacteon affinis Borgmeier, Pseudacteon dentiger Borgmeier and Pseudacteon disneyi Pesquero were created in a laboratory from parasitized workers of S. saevissima. The other phorid species grew only until the pupa phase due to low temperature and humidity when kept in a climatic chamber. Pseudacteon cultellatus Borgmeier was more efficient than the other species, taking 12 days to kill the host workers. Similar to the group of phorid species parasitizingSolenopsis invicta Buren, the daily period of activity and body size are important factors to be considered in the use of these natural enemies in future programs of biological control of S. saevissima.